1989
DOI: 10.1177/00220345890680110601
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Characterization of Sensitive vs. Insensitive Human Radicular Dentin

Abstract: Our aim was to investigate the structural changes of dentinal tubules in specimens obtained from both hypersensitive and naturally desensitized areas in wedge-shaped defects on the same exposed cervical dentin surface of a hypersensitive tooth. A new biopsy technique that makes use of a hollow, cylindrical diamond bur was designed so that specimens from exposed root dentin of vital teeth could be obtained. Twenty-two dentin biopsy pairs were divided into two groups; one was prepared for scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
29

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 12 publications
4
81
0
29
Order By: Relevance
“…The present work demonstrated that important details of dentin surfaces treated with desensitizing agents may be identified in SEM micrographs at the relatively low magnification of 1000x. This non-invasive procedure may be useful in clinical trials in substitution for dentin biopsy (20) or extraction of teeth for direct observation (9).…”
Section: Discussionmentioning
confidence: 99%
“…The present work demonstrated that important details of dentin surfaces treated with desensitizing agents may be identified in SEM micrographs at the relatively low magnification of 1000x. This non-invasive procedure may be useful in clinical trials in substitution for dentin biopsy (20) or extraction of teeth for direct observation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Fig.11b is a 'dentin biopsy' of the surface layer with higher mineral content examined in a scanning electron microscope showing that mineral salts have precipitated in the tubules. Source: Yoshiyama et al (10). Fig.…”
Section: Branches Of the Dentinal Tubulesmentioning
confidence: 99%
“…Although the mechanisms of pain transmission across dentin are not fully understood, dentin sensitivity is reduced by reduction of permeability and occlusion of dentinal tubules 4,5) . The exposed patent dentinal tubule is considered the morphological etiology of dentin hypersensitivity; in vivo studies revealed that the orifices of many dentinal tubules in hypersensitive areas were open 6,7) . However, different types of hypersensitive dentin express different surface characteristics.…”
Section: Introductionmentioning
confidence: 99%